Charles H. Houston an interdisciplinary study of civil rights leadership - Houston, Charles Hamilton, 1895-1950.; Conyers, James L.; ebrary, Inc. (Lanham [Md.] : Lexington Books, 2012)
"This edited collection focuses on the philosophical ideas, constructive engagement, and lasting contributions of Charles H. Houston, a legal scholar activist who played an important role in the civil rights movement"--
Machine generated contents note: Chapter 1: Charles Hamilton Houston: An Efficacious Reflexive Analysis -- James L. Conyers, Jr. -- Part I. Philosophical Foundations -- Chapter 2: In Defense of Voluntary Desegregation: All Things Are Not Equal -- Derek W. Black -- Chapter 3: "A Lawyer is either a social engineer or a parasite to society" -- John Brittain -- Chapter 4: What the Right Learned from Charles Houston That the Left Did Not -- Lewis R. Gordon -- Part II. Constructive Engagement -- Chapter 5: The Historical Legacy of the Nadir and Houstonian Jurisprudence in the -- Origins of the Modern Civil Rights Movement -- Katherine Bankole Medina -- Chapter 6: Charles Hamilton Houston and Post-New Negro Movement Authority: -- The Socio-Literary History of a Legal Warrior -- Christel N. Temple -- Part III. Enduring Contributions -- Chapter 7: Charles Hamilton Houston and the Struggle Against Lynching in the -- United States, 1930-1939 -- Julius E. Thompson -- Chapter 8: African American Voices Should Speak Loudly and Proudly to Protect Undocumented Immigrants from Fundamentally Unfair Discrimination -- L. Darnell Weeden -- Chapter 9: Charles Hamilton Houston and the Development of the NAACP's Legal Assault on Jim Crow: The Texas White Primary as a Case Study -- Cary D. Wintz -- Chapter 10: Neo-Houstonian Studies: The Nation of Islam, Edward W. Jacko, Jr. and the Struggle for Afro-Muslim Civil Liberties -- Malachi Crawford.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: African Americans -- Civil rights -- History; Civil rights movements -- United States -- History; United States -- Race relations -- History; Electronic books